PEMIKIRAN NEO-SUFISME SYAIKH AHMAD AL-MUTAMAKKIN - Manggara Bagus Satriya Wijaya; Sariyatun Sariyatun (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2018)
This article intends to reveal Syaikh Ahmad al-Mutamakkin's neo-Sufism thoughts and his role in campaigning for the renewal of Islamic thought and changes in the social order of people's lives in Java in the 18th century. The discussion will focus on the domain of epistemological conflicts that legitimize al-Mutamakkin as a controversial contemporary Sufi. Historical exploration and appreciation will be more emphasized to fully look for facts about the teachings developed by al-Mutamakkin. This research is historical research using a hermeneutic approach to study and trace the artifacts of al-Mutamakkin's thoughts. This study found that al-Mutamakkin was a reformist figure who played an active role in upholding Islamic teachings as a universal religion and eternal through an eclectic and conformist approach to the existence of local wisdom values (local wisdom). As a reformist figure who carried the breath of renewal of the teachings of Sufism (neo-Sufism), al-Mutamakkin strongly criticized the teachings of Sufism developed by the Mataram elite. The king-Sufi political conception commonly adopted by the court elite in the 18th century in al-Mutamakkin's perspective was a form of betrayal of the teachings of Sufism. Therefore, in his perspective, the teachings of Sufism must be improved and adjusted to the proper khittah, namely as an instrument of self-formation and development of perfect human beings (insān kāmil) which is adjusted and guided by Allah's revelation and the Prophet's Sunnah.